Optimization of air mass flow in a PEM fuel cell - Novotný Jan; Nováková Ludmila; Čížek Roman; Kašpárek Miloš; Machovská Ilona (EPJ Web of Conferences, 2022)
In our work, we focused on measuring the performance characteristics of a test hydrogen fuel cell with an open cathode. The aim of the work was to verify the effect of the mass flow through the fuel cell on the power output as a function of the current density and voltage on the fuel cell. A test bench capable of testing fuel cells up to 2000 W was used to measure the power characteristics. The test fuel cell was composed of three cells and its total membrane area was 100 cm2. A PIV measurement system was used to measure the mass flow. The mass flow measurement was performed at the inlet of the fuel cell. The measurements included the determination of the inlet temperature distribution using a thermal imaging camera. The presented measurements were performed for two configurations with original and optimized diffuser at the inlet of the fans. Finally, the effect of mass flow and overall thermal management on the fuel cell performance is discussed, including the effect of the newly designed diffuser.